Implementation of Environmental Accounting in a Halal Manufacturing Company: Implementasi Akuntansi Lingkungan di Perusahaan Manufaktur Halal - Sunni Syahputra; Yenni Samri Juliati Nasution; Hendra Harmain (Academia Open, 2025)
General Background: The halal industry is expanding globally, driven by increasing awareness of ethical, hygienic, and spiritually aligned production standards. Specific Background: In Indonesia, as a key player in the halal economy, the integration of Islamic values into business practices is emphasized, including environmental accountability. Knowledge Gap: However, practical implementation of sharia-based environmental accounting remains limited, especially in halal manufacturing sectors. Aims: This study investigates the application of environmental accounting at PT Kimia Farma in the Medan Industrial Area, focusing on the integration of maqashid sharia principles. Results: Findings show that while the company implements environmental initiatives—such as waste treatment, energy efficiency, and CSR—it lacks a formal environmental accounting framework grounded in Islamic accountability. Novelty: Using stakeholder theory and Islamic accountability theory, the research presents empirical insights into the gap between normative values and structured sharia reporting, highlighting both institutional strengths (halal certification, managerial commitment) and constraints (lack of technical guidance, limited human resource capacity). Implications: The study underscores the urgency of developing sharia-compliant environmental reporting models to strengthen ethical governance in halal industries, offering strategic insights for policymakers, regulators, and halal enterprises seeking sustainability through faith-based accountability.Highlight : The study explores environmental accounting implementation in the halal industry using a case study of PT Kimia Farma. Findings show the absence of a structured sharia-based reporting system despite internal Islamic values. Key barriers include lack of technical guidelines and limited literacy in maqashid shariah among staff. Keywords : Environmental Accounting, Halal Industry, Maqashid Shariah, Islamic Accountability, PT Kimia Farma